Applicability of tourism impact assessment methods - Pénzes, Erzsébet (JOURNAL OF LANDSCAPE ECOLOGY, 2009)
Nature based tourism needs to consider not only effective planning, but also monitoring, environmental auditing and impact assessment.Tourism researchers and managers increasingly emphasize the necessity of impact assessment in tourism, the need to measure impacts of tourism. On the one hand, measuring and handling the impacts are the elements of sustainability and on the other, it provides the basis for development and planning. The aim of this research was to identify and work out impact assessment methods and then create a framework methodology for tourism managers to help them with selecting the best method and to start measuring the environmental impacts and the state of the tourism infrastructure. Most of the methods have to be operated by tourism managers - who do not have any qualification in natural sciences, thus, it was considered, which methods they can most easily apply.After appraising and systematizing the methods, I shaped a new methodology for choosing the best method for a given situation and location. In the course of a multi-stage decision process the tourism managers will be able to select the best assessment method they need to apply to measure the impacts of tourism.
Keywords: nature based tourism; impact assessment; carrying capacity; tourism